2019
DOI: 10.1073/pnas.1821194116
|View full text |Cite
|
Sign up to set email alerts
|

The VEGF receptor neuropilin 2 promotes homologous recombination by stimulating YAP/TAZ-mediated Rad51 expression

Abstract: Vascular endothelial growth factor (VEGF) signaling in tumor cells mediated by neuropilins (NRPs) contributes to the aggressive nature of several cancers, including triple-negative breast cancer (TNBC), independently of its role in angiogenesis. Understanding the mechanisms by which VEGF–NRP signaling contributes to the phenotype of such cancers is a significant and timely problem. We report that VEGF–NRP2 promote homologous recombination (HR) in BRCA1 wild-type TNBC cells by contributing to the expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…21 Moreover, TAZ was found to contribute to Rad51 expression and promote homologous recombination in breast cancer. 22 Collectively, these studies strongly support the idea that Hippo signaling pathway activation is closely associated with oncogenesis and cancer radioresistance.…”
Section: Introductionsupporting
confidence: 58%
“…21 Moreover, TAZ was found to contribute to Rad51 expression and promote homologous recombination in breast cancer. 22 Collectively, these studies strongly support the idea that Hippo signaling pathway activation is closely associated with oncogenesis and cancer radioresistance.…”
Section: Introductionsupporting
confidence: 58%
“…Because we observed that YAP inhibition decreased HSPA12B mRNA levels ( Figure 4G ), we next investigated whether HSPA12B was a direct transcriptional target of YAP in HUVECs. YAP controls gene transcription via binding to TEAD around the promoter or enhancer of target genes ( 36 , 37 ). Therefore, we searched for and identified TEAD4-binding motif in the HSPA12B gene-enhancer regions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, YAP and TAZ function as oncogenes via translocation into nucleus during cancer metastasis 36 . OTUB2 deubiquitinates YAP/TAZ for cancer metastasis 37 , and YAP/TAZ-mediated Rad51 expression facilitates for HR during resistance to platinum chemotherapy 38 . Therefore, YAP/TAZ signaling pathway might be involved in OTUB2-mediated HR in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%